SAMMAZ 60: A new vitamin A biofortified maize variety in Nigeria - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Collaboration between HarvestPlus, CGIAR breeding centers, and NARS resulted in the release of 23 new varieties of 7 biofortified crops in 9 countries, in 2020. Evidence provided links to the biofortification crops map. An internal HarvestPlus database along with breeding reports can be made available upon request.